Analysis of construction methods for the Kra-canal excavation - Liang, Alexander Su Fat; Chauhan, Roshan Lal; Ueda, Tamon; Jearkjirm, Vithool; Government of F.R. of Germany (Bangkok : Asian Institute of Technology, 1990)
An attempt has been made in this study to anallse the application of several construction methods using different combinations of equipment, such as dragline-dump trucks, dragline-belt conveyor system, s hove l-dump trucks , shovel-be ! t conveyor system, dredger-:-barges , dredger-pipe line system, railroad equipment, bucket wheel excavator, and scrape r-pushers in the Kra-canal excavation works. The canal alignment is divided into several sections; chainage km 0 - 2, km 2 - 5, km 5 - 13, km 13 - 20, km 20 - 75, km 75 - 102 based on the material encountered in each section. The equipment selected to be used in each section depends on its suitability and ability to perform the required excavation and transportation operation in the existing ground condition. Because huge quantities of earth are to be moved, economy can be achieved only by using big sized tailor-made equipment. Theoretic al production and unit cost of moving the earth for each system were calculated using queueing theory . The optimum allocation of material from different sources to different destinations for chainage km 20 - 75 we re then determined using the uni t costs obtained from the application of queueing models and by applying the transportation mode ls. The total cost of earth- moving for each chainage were calculated based on the quantities derived f rom the canal cross sections and the unit cost s for different methods . These costs were then compared to select that combination of equipment which gives the optimum costs. It was found that a combination of dragline-conveyor system, shove l - trucks , dragline-conveyor system, shove l - dump trucks, s hove l-dump trucks, and shovel - belt conveyor system respectively are the cheapest options for chainage km 0 - 2, km 5 - 13, km 13 - 20, km 20 - 75, km 75 - 102.
A thesis submitted in partial fulfillments of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1990
Keywords: Kra Canal